Seasonal Variation of Ekman Transport in the Southern Waters of West Sumatra - Agustina Siregar; Anjasman Anjasman; Septi Johan; Siti Hairunnisa Norfahmi; Lizalidiawati Lizalidiawati (Jurnal Kelautan Tropis, 2026)
This study examines seasonal variations in Ekman transport in the southern waters of western Sumatra using wind, ocean current, and sea level data from the Copernicus Marine Service for the period 2023–2024.  Data analysis was conducted spatially and temporally using Panoply, Python, and ArcGIS software. The results show that Ekman transport dynamics are significantly influenced by changes in the direction and intensity of the Asian–Australian monsoon winds. Maximum transport values were identified in the East Season at 4-5 m3/s due to strengthening southeasterly winds, while minimum values occurred in the West Season at 1-2 m3/s when westerly winds dominated the region. These seasonal variations show a close relationship with changes in surface currents and sea level, reflecting the dynamic response of the oceanographic system to the influence of wind friction. These results reinforce the understanding that Ekman transport plays an essential role in controlling regional ocean circulation patterns and provides an important scientific basis for marine resource management in the waters west of Sumatra.